English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2007-01-28 15:53:18 · 4 answers · asked by rosemariestewart64 1 in Science & Mathematics Mathematics

4 answers

x^2-3xyz+4
(-3)^2-3(-3)(1)(1)+4
9+9+4
22

2007-01-28 15:56:51 · answer #1 · answered by Bill F 6 · 0 0

To solve, plug in the values that are given for the variables
x^2-3xyz+4
(-3)^2-3(-3)(1)(1)+4
Evaluate
9+9+4=22

2007-01-29 00:00:27 · answer #2 · answered by tval_friedly 2 · 0 0

f(x,y,z)=x^2 - 3xyz +4
f(-3,1,1)=?

f(-3,1,1)=(-3)^2-3(-3) .1 . 1+4
=9+9+4
=22

2007-01-29 00:06:23 · answer #3 · answered by iyiogrenci 6 · 0 0

22...bill's right

2007-01-29 00:01:15 · answer #4 · answered by Anonymous · 0 0

fedest.com, questions and answers